SakA and MpkC Stress MAPKs Show Opposite and Common Functions During Stress Responses and Development in Aspergillus nidulans - Garrido-Bazán, Verónica; Jaimes-Arroyo, Rafael; Sánchez, Olivia; Lara-Rojas, Fernando; Aguirre, Jesús (Frontiers in Microbiology, 2018)
Stress activated MAP kinases (SAPKs) of the Hog1/Sty1/p38 family are specialized in transducing stress signals. In contrast to what is seen in animal cells, very few fungal species contain more than one SAPK. Aspergillus nidulans and other Aspergilli contain two SAPKs called SakA/HogA and MpkC. We have shown that SakA is essential for conidia to maintain their viability and to survive high H2O2 concentrations. H2O2 induces SakA nuclear accumulation and its interaction with transcription factor AtfA. Although SakA and MpkC show physical interaction, little is known about MpkC functions. Here we show that ΔmpkC mutants are not sensitive to oxidative stress but in fact MpkC inactivation partially restores the oxidative stress resistance of ΔsakA mutants. ΔmpkC mutants display about 2-fold increase in the production of fully viable conidia. The inactivation of the SakA upstream MAPKK PbsB or the simultaneous elimination of sakA and mpkC result in virtually identical phenotypes, including decreased radial growth, a drastic reduction of conidiation and a sharp, progressive loss of conidial viability. SakA and to minor extent MpkC also regulate cell-wall integrity. Given MpkC roles in conidation and oxidative stress sensitivity, we used a functional MpkC::GFP fusion to determined MpkC nuclear localization as an in vivo indicator of MpkC activation during asexual development and stress. In intact conidia MpkC is mostly localized in the cytoplasm, accumulates in nuclei during the first 2 hours of germination and then becomes progressively excluded from nuclei in growing hyphae. In the conidiophore, MpkC nuclear accumulation increases in vesicles, metulae and phialides and decreases in older conidia. Oxidative and osmotic stresses induce MpkC nuclear accumulation in both germinating conidia and hyphae. In all these cases, MpkC nuclear accumulation is largely dependent on the MAPKK PbsB. Our results indicate that SakA and MpkC play major, distinct and sometimes opposing roles in conidiation and conidiospore physiology, as well as common roles in response to stress. We propose that two SAPKs are necessary to delay (MpkC) or fully stop (SakA) mitosis during conidiogenesis and the terminal differentiation of conidia, in the highly prolific phialoconidiation process characteristic of the Aspergilli.